Achieving stable mainstream deammonification process by a novel combinatorial control strategy. (December 2020) - Li, Yuqi; Xiang, Tao; Liang, Hong; Gao, Dawen; Wang, Peng
Graphical abstract: Highlights: A control strategy was proposed to maintain stable mainstream deammonification. High nitrogen removal performance was achieved in the treatment of domestic sewage. Temperature and C/N were identified as two factors affecting nitrogen removal pathways. The deammonification was main nitrogen removal pathway in treating domestic sewage. Abstract: In this study, a novel combinatorial control strategy was developed to guarantee a stable mainstream deammonification process, with three critical steps including (a) upflow airwater washing, (b) short-term increased nitrogen loading rate (NLR), and (c) low oxygen supply. Results showed that two upflow double-blanket filter (UDBF) reactors effectively performed the mainstream deammonification process with the nitrogen removal efficiency (NRE) 84.5 ± 2.2% and 84.6 ± 1.6%, respectively and nitrogen removal rate (NRR) 123.8 ± 2.9 and 125.5 ± 6.2 g N·(m 3 ·d) −1, respectively. Statistically, temperature and C/N were considered as two vital factors affecting the nitrogen removal pathways, which co-explained 80.9% and 78.4% of the maximum possible contribution of heterotrophic denitrification in both reactors. The deammonification process accounted for more than 59.8% of TN removal in R2 and 54.8% in R1, which cooperated well with heterotrophic denitrification for efficient performance in treating municipal sewage.